Implied correlations of iTraxx tranches during the financial crisis - Thomas Heidorn; Dennis Kahlert (Frankfurt School of Finance & Management, 2010)
Implied Base Correlations of Single-tranche CDOs on standardized Credit Indices such as the iTraxx Europe have been used in the credit derivatives market for price communication. During the financial crisis, implied correlations have been quite volatile indicating the growing fraction of systematic credit risk of STCDOs. This paper analyses the determinants of tranche implied base correlations for the period September 2006 until April 2009. It will be shown that realized asset correlations between iTraxx Europe corporates are not able to explain the extreme movements of tranche implied correlations during the financial crisis. Additionally, it will be seen that the worsening creditworthiness of market participants in the interbank market as well as growing pressure on their refinancing conditions correlated significantly with the development of implied base correlations of iTraxx tranches.
Keywords: 330; Implied Correlation; Asset Correlation; Systematic Credit Risk; Market Liquidity; Funding Liquity; Asset-backed security; Börsenkurs; Kreditrisiko; Marktliquidität; Korrelation; Schätzung; Finanzmarktkrise; Europa